A case series of epidermoid cysts of external ear in paediatric age group at our tertiary institution - Mane, Balaji Shankarrao; Tidake, Abasaheb Madhukar; Gavali, Rushali Madhukar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Epidermoid cyst is a benign, small, subcutaneous, extremely rare, developmental cyst of head and neck region. Case series analysis with duration of one year from June 2021 till June 2022 with study population comprised of five- patients in the paediatric age group that is age ≤12 years with epidermoid cyst over the external ear. All of our cases were benign and asymptomatic in nature and without any recurrence in follow up while the case one and five were having large size with the gross deformity of external ear which is uncommon. The histopathological examination in all cases shown fibro-collagenous cyst wall lined by keratinizing stratified squamous epithelium with a prominent granular cell layer with abundant keratin flakes. All cases shown successful surgical outcome which was confirmed by lack of postsurgical alterations and no recurrence of the lesion during follow up of next 6 months.